2015
DOI: 10.1027/1618-3169/a000287
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Multinomial Modeling Approaches

Abstract: Hierarchical extensions of multinomial processing tree (MPT) models have been developed to deal with heterogeneity in participants or items. In this study, the beta-MPT model (J. B. Smith & Batchelder, 2010) and the latent-trait approach (Klauer, 2010) were used to estimate individual model parameters for prospective and retrospective components of prospective memory (PM), which requires remembering to perform an action in the future. The data from two experiments investigating the relationship between PM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
(115 reference statements)
2
7
0
Order By: Relevance
“…These tasks likely overloaded WM and executive resources, particularly when participants were required to inhibit stereotypic sequences (e.g., 1-2-3, 2-4-6) while monitoring their output to comply with the randomness condition ( Baddeley et al, 1998 ). These findings are consistent with prior research indicating that poor PM performance is linked to impaired WM ( Arnold et al, 2015 ; Rose et al, 2010 ), planning (e.g., Shum et al, 2013 ), inhibition, or task-switching abilities (e.g., Schnitzspahn et al, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…These tasks likely overloaded WM and executive resources, particularly when participants were required to inhibit stereotypic sequences (e.g., 1-2-3, 2-4-6) while monitoring their output to comply with the randomness condition ( Baddeley et al, 1998 ). These findings are consistent with prior research indicating that poor PM performance is linked to impaired WM ( Arnold et al, 2015 ; Rose et al, 2010 ), planning (e.g., Shum et al, 2013 ), inhibition, or task-switching abilities (e.g., Schnitzspahn et al, 2013 ).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous research which has shown that state and trait rumination are related to impairments in working memory, inhibition and set-shifting (De Lissnyder et al, 2010;De Lissnyder et al, 2011;Watkins & Brown, 2002). While all these cognitive processes are involved in PM (Arnold et al, 2015;Kliegel et al, 2008), to our knowledge this is the first study to show a specific relationship between state rumination and impaired PM cue detection, and trait brooding and impaired response times to PM cues.…”
Section: Discussionsupporting
confidence: 92%
“…In previous analyses, parameter estimates for the beta-MPT model were often similar to those for the latent-trait MPT model (e.g., Arnold, Bayen, & Smith, 2015 ). Table 1 shows the results of both analyses for the retrieval condition from Arnold et al ( 2013 ).…”
Section: Treebugsmentioning
confidence: 58%